Charge‐transfer‐induced doping at an electron donor (α‐sexithiophene)/acceptor (C60) interface and mobility improvement. Issue 1 (5th November 2013) - Park, Byoungnam; Park, Jonghoo
Abstract We studied various aspects relating to surface charge‐transfer‐induced doping at an organic/organic interface using in situ electrical measurements with a field‐effect transistor (FET) during the formation of the electron donor/acceptor interface. Adsorption of the electron‐accepting molecules (C60) on top of the electron donating molecules (α‐6T) led to an increase in the FET hole mobility in an α‐6T film. Under illumination, the FET hole mobility in the α‐6T film with C60 deposition was significantly increased in comparison with that in the dark due to exciton dissociation at the C60/α‐6T interface, resulting in a large threshold voltage shift. The origin of the mobility increase is explained by the multiple trapping and release (MTR) model in which the mobility is determined by the carrier density. Various phenomena relevant to charge transfer and charge transport at the organic/organic interface are reported and their origins are discussed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)